The Influence of Employee Engagement and Normative Commitment on Organizational Citizenship Behavior Of Civil Servants at the Forest Area and Environmental Management Office Regional III Pontianak - Madina, Madina; Arninda, Arninda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the influence of Employee Engagement and Normative Commitment on Organizational Citizenship Behavior (OCB) among Civil Servants at the forest area and environmental management office regional III Pontianak. The underlying phenomenon of this study is the high level of absenteeism associated with poor work discipline, as well as how Employee Engagement and Normative Commitment can influence positive additional behavior beyond employees' formal duties. This study uses a quantitative approach with data obtained through interviews and the distribution of questionnaires to all employees in the office. The population in this study consists of 36 civil servants at the forest area and environmental management office regional III Pontianak. The sampling technique used was saturated sampling, where all members of the population were included in the sample. The analysis methods used were multiple linear regression, double correlation coefficient analysis (R), coefficient of determination, simultaneous test (F-test), and partial test (t-test). The results of the study indicate that Employee Engagement and Normative Commitment have a strong relationship with Organizational Citizenship Behavior. The F-test results show that Employee Engagement and Normative Commitment have a significant simultaneous effect on OCB. The t-test results show that Employee Engagement and Normative Commitment partially have a positive and significant effect on Organizational Citizenship Behavior (Y). Based on the results of this study, it is recommended that organizations focus on increasing Employee Engagement and strengthening Normative Commitment to create positive behavior that has a direct impact on performance and harmony within the organization.